Ammonium [11C]thiocyanate: revised preparation and reactivity studies of a versatile nucleophile for carbon-11 radiolabelling. Issue 8 (2nd July 2018) - Haywood, Tom; Cesarec, Sara; Kealey, Steven; Plisson, Christophe; Miller, Philip W.
Abstract : Ammonium [ 11 C]thiocyanate, produced from [ 11 C]CS2, was used to efficiently radiolabel a range of C-11 thiocyanate and thiazolone molecules. Abstract : Herein we report the preparation of ammonium [ 11 C]thiocyanate via the reaction of [ 11 C]CS2 with ammonia. The [ 11 C]SCN − ion is demonstrated as a potent nucleophile that can be used to readily generate a range of 11 C-labelled thiocyanate molecules in high conversions. Furthermore, novel 11 C-labelled thiazolone molecules can be easily prepared from the intermediate α-thiocyanatophenones via an acid mediated cyclisation reaction.